Immune oxysterols: Role in mycobacterial infection and inflammation. Issue 169 (May 2017) - Bah, Saikou Y.; Dickinson, Paul; Forster, Thorsten; Kampmann, Beate; Ghazal, Peter
Graphical abstract: Highlights: Oxidised cholesterol as effectors of immunity to infection. Immune modulation of oxysterols. 1, 25 dihydroxyvitamin D and 25 hydroxycholesterol highlight immune metabolic-axis for TB. Abstract: Infection remains an important cause of morbidity and mortality. Natural defenses to infection are mediated by intrinsic/innate and adaptive immune responses. While our understanding is considerable it is incomplete and emerging areas of research such as those related to the immune-metabolic axis are only beginning to be appreciated. There is increasing evidence showing a connection between immune signalling and the regulation of sterol and fatty acid metabolism. In particular, metabolic intermediates of cholesterol biosynthesis and its oxidized metabolites (oxysterols) have been shown to regulate adaptive immunity and inflammation and for innate immune signalling to regulate the dynamics of cholesterol synthesis and homeostasis. The side-chain oxidized oxysterols, 25-hydroxycholesterol (25HC) and vitamin D metabolites (vitamin D3 and vitamin D2 ), are now known to impart physiologically profound effects on immune responses. Macrophages play a frontline role in this process connecting immunity, infection and lipid biology, and collaterally are a central target for infection by a wide range of pathogens including viruses and bacteria, especially intracellular bacteria such as mycobacteria. Clinical manifestations of disease severity in the infected host are likely to pay tribute to perturbations of the metabolic-immune phenomena found in lymphocytes and myeloid cells. Historically and consistent with this notion, vitamin D based oxysterols have had a long association with promoting clinical improvements to patients infected with Mycobacterium tuberculosis . Hence understanding the role of early metabolic mediators of inflammatory responses to infection in particular oxysterols, will aid in the development of urgently needed host directed therapeutic and diagnostic design innovation to combat adverse infection outcomes and antibiotic resistance.